Genome Analysis of Phage JS98 Defines a Fourth Major Subgroup of T4-Like Phages in Escherichia coli - Zuber, Sophie (American Society for Microbiology (ASM), 2007)
Numerous T4-like Escherichia coli phages were isolated from human stool and environmental wastewater samples in Bangladesh and Switzerland. The sequences of the major head gene (g23) revealed that these coliphages could be placed into four subgroups, represented by the phages T4, RB69, RB49, and JS98. Thus, JS98 defines a new major subgroup of E. coli T4-like phages. We conducted an analysis of the 169-kb JS98 genome sequence. Overall, 198 of the 266 JS98 open reading frames (ORFs) shared amino acid sequence identity with the reference T4 phage, 41 shared identity with other T4-like phages, and 27 ORFs lacked any database matches. Genes on the plus strand encoded virion proteins, which showed moderate to high sequence identity with T4 proteins. The right genome half of JS98 showed a higher degree of sequence conservation with T4 and RB69, even for the nonstructural genes, than did the left genome half, containing exclusively nonstructural genes. Most of the JS98-specific genes were found in the left genome half. Two came as a hypervariability cluster, but most represented isolated genes, suggesting that they were acquired separately in multiple acquisition events. No evidence for DNA exchange between JS98 phage and the E. coli host genome or coliphages other than T4 was observed. No undesired genes which could compromise its medical use were detected in the JS98 genome sequence.